Solvability in Holder Space of an Initial Boundary Value Problem for the Time-Fractional Diffusion - Krasnoschok, M.V. (Журнал математической физики, анализа, геометрии, 2016)
In this paper we consider an initial boundary value problem for the timefractional diffusion equation with mixed boundary conditions. We prove a theorem of existence and uniqueness of solution to this problem in Hölder spaces. Рассмотрена начально-краевая задача для уравнения диффузии с дробной производной по времени со смешанными граничными условиями. Доказана теорема существования и единственности решения этой задачи в пространствах Гёльдера.